CRYSTAL-MELT EQUILIBRIA INVOLVING POTASSIUM-BEARING CLINOPYROXENE AS INDICATOR OF MANTLE-DERIVED ULTRAHIGH-POTASSIC LIQUIDS: AN ANALYTICAL REVIEW - Perchuk L.L.; Safonov O.G.; Yapaskurt V.O.; Barton Jr.J.M. (My University, 2002)
Crystal–liquid equilibria, including phase relationships of minerals with silicate and/or carbonate melts, are reviewed in order to understand the occurrence of clinopyroxene with up to 2 wt.% K2O (KCpx). This mineral occurs as inclusions in diamond from kimberlite pipes and in garnet from garnet–clinopyroxene potassium-poor silicate rocks intercalated with diamondiferous silicate–carbonate rocks of the Kokchetav Complex, northern Kazakhstan. The analysis of the available experimental data allowed estimation of the effect of P, T and compositional parameters on the equilibrium of KAlSi2O6 (in Cpx)=1/4K4Si2O6+3/4Al4/3Si2O6 (in melt) in various silicate systems. A strong dependence of the K2O partition coefficient both on pressure and SiO2 and Al2O3 contents in the melt was identified and thermodynamically described. The resulting thermodynamic equation allows the calculation of pressure of the KCpx formation within interval 50–100 kbar for known melt compositions.
Keywords: Mineral equilibria; Potassium-bearing clinopyroxene; Inclusions; Mantle; Melting relations